Effects of cannabinoid drugs on the deficit of prepulse inhibition of startle in an animal model of schizophrenia: the SHR strain - Levin, Raquel; Peres, Fernanda F.; Almeida, Valéria; Calzavara, Mariana B.; Zuardi, Antonio W.; Hallak, Jaime E.; Crippa, José Alexandre S.; Abílio, Vanessa C. (Frontiers in Pharmacology, 2014)
Clinical and neurobiological findings suggest that the cannabinoids and the endocannabinoid system may be implicated in the pathophysiology and treatment of schizophrenia. We described that the Spontaneously Hypertensive Rats (SHR) strain presents a schizophrenia behavioral phenotype that is specifically attenuated by antipsychotic drugs, and potentiated by proschizophrenia manipulations. Based on these findings, we have suggested this strain as an animal model of schizophrenia. The aim of this study was to evaluate the effects of cannabinoid drugs on the deficit of prepulse inhibition of startle (PPI), the main paradigm used to study sensorimotor gating impairment related to schizophrenia, presented by the SHR strain. The following drugs were used: 1) WIN55212,2 (cannabinoid agonist), 2) rimonabant (CB1 antagonist), 3) AM404 (anandamide uptake inhibitor), and 4) cannabidiol (indirect CB1/CB2 receptor antagonist, among other effects). Wistar rats (WR) and SHRs were treated with vehicle or different doses of WIN55212 (0.3, 1 or 3 mg/kg), rimonabant (0.75, 1.5 or 3 mg/kg), AM404 (1, 5 or 10 mg/kg) or cannabidiol (15, 30 or 60 mg/kg). Vehicle-treated SHRs showed a decreased PPI when compared to WRs. This PPI deficit was reversed by 1 mg/kg WIN and 30 mg/kg cannabidiol. Conversely, 0.75 mg/kg rimonabant decreased PPI in SHR strain, whereas AM404 did not modify it. Our results reinforce the role of the endocannabinoid system in the sensorimotor gating impairment related to schizophrenia, and point to cannabinoid drugs as potential therapeutic strategies.